PREPARATION AND EVALUATION OF HERBO-MINERAL DRUG: AROGYAVARDHINI VATI (TABLET) - Lanjewar, *Ranjana Maroti; Raman, Belge; Sarang, Deshpande; Tarun, Pable (International Journal of Ayurveda and Pharma Research, 2017)
As per ancient Ayurveda scholars for getting desirable outcome of any medication, it should be precisely analyzed before prescribing to the patient. In maximum cases there is lack of data regarding their detailed standardized pharmaceutical procedures. Arogyavardhini vati is one of the herbo-mineral drugs which are widely used by Ayurveda physicians for the treatment of skin disorders and hepatic diseases. Medicines prepared using traditional method may not have the desired quality and batch to batch consistency. Hence, there is a need of Pharmaceutical and analytical validation of the formulations on Ayurvedic as well as modern parameters. Arogyavardhini vati is traditionally used in Vati form in this study efforts were made to transform it into tablet dosage form. The present work deals with the preparation of Arogyavardhini vati in tablet form using modern equipments and techniques. Pharmacopeial standards are set for the Ayurvedic formulations in tablet form. Three batches of the sample were prepared and their analytical validation was set. All the three batches are identical and do not show any significant difference in their analytical parameters. HPTLC fingerprinting also shows similar Rf values which confirms the product prepared by this method is authentic. The set parameters may be used as reference parameters for further pharmaceutical processes.